Vincristine chemotherapy trials and pharmacokinetics in tasmanian devils with tasmanian devil facial tumor disease. - David N Phalen (Public Library of Science (PLoS), 2013)
Tasmanian Devil Facial Tumor Disease (DFTD) is a transmissible cancer threatening to cause the extinction of Tasmanian Devils in the wild. The aim of this study was to determine the susceptibility of the DFTD to vincristine. Escalating dosage rates of vincristine (0.05 to 0.136 mg/kg) were given to Tasmanian devils in the early stages of DFTD (n = 8). None of these dosage rates impacted the outcome of the disease. A dosage rate of 0.105 mg/kg, a rate significantly higher than that given in humans or domestic animals, was found to the highest dosage rate that could be administered safely. Signs of toxicity included anorexia, vomiting, diarrhea and neutropenia. Pharmacokinetic studies showed that, as with other species, there was a rapid drop in blood concentration following a rapid intravenous infusion with a high volume of distribution (1.96 L/kg) and a relatively long elimination half life (11 h). Plasma clearance (1.8 ml/min/kg) was slower in the Tasmanian devil than in humans, suggesting that pharmacodynamics and not pharmacokinetics explain the Tasmanian devil's ability to tolerate high dosage rates of vincristine. While providing base-line data for the use of vincristine in Tasmanian devils and possibly other marsupials with vincristine susceptible cancers, these findings strongly suggest that vincristine will not be effective in the treatment of DFTD.